2015
DOI: 10.1519/jsc.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Anthropometric, Strength, and Muscle Power Characteristics Correlates With Running Performance in Young Runners

Abstract: The purpose of this study was to investigate the relationship between physiological, anthropometric, strength, and muscle power variables and a 5-km time trial (5kmT) in young runners. Twenty-three runners volunteered to participate in this study. Height, body mass, body fat, and fat-free mass (FFM) were measured. The subjects underwent laboratory testing to determine maximal oxygen uptake ((Equation is included in full-text article.)), velocity at ventilatory threshold (VVT), running economy (RE), velocity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…In other sports, progress is often monitored by physiological and/or fitness tests, and their performance can be partially predicted by physiological and/or muscle performance data. 6 , 7 Given that CrossFit competition involves using many aspects of fitness in a sport environment, it is possible that performance can be at least partially explained by physiological measures, which would have implications for directing training program design.…”
Section: Introductionmentioning
confidence: 99%
“…In other sports, progress is often monitored by physiological and/or fitness tests, and their performance can be partially predicted by physiological and/or muscle performance data. 6 , 7 Given that CrossFit competition involves using many aspects of fitness in a sport environment, it is possible that performance can be at least partially explained by physiological measures, which would have implications for directing training program design.…”
Section: Introductionmentioning
confidence: 99%
“…La asociación existente entre las variables antropométricas y de composición corporal con la potencia de salto vertical han sido estudiadas por Pérez-López et al 12 . En esta misma línea, otro estudio demostró una correlación inversa del salto vertical con el % de masa grasa 24 . A pesar de que estudios previos se centran en el estudio del % de grasa y su relación con el rendimiento y el nivel de fatiga 25 , nuestros resultados sugieren que también hay que tener en cuenta otras variables tales como el porcentaje de masa muscular.…”
Section: Discussionunclassified
“…It partially corroborate with previous study conducted with long distance runners where a significant difference was observed in running speeds between iRER 1.0 and VT 2 5 . Regarding that aerobic-anaerobic transition is related with endurance performance 25 , some studies showed that RER values above 1.0 were correlated with running pace (speed) during competition 26 . It could be a possible elucidation for aerobic capacity overestimation using iRER 1.0 .…”
Section: Discussionmentioning
confidence: 99%